2022
DOI: 10.1111/ajt.17117
|View full text |Cite
|
Sign up to set email alerts
|

The risk and consequences of breakthrough SARS-CoV-2 infection in solid organ transplant recipients relative to non-immunosuppressed controls

Abstract: Clinical outcomes in solid organ transplant (SOT) recipients with breakthrough COVID (BTCo) after two doses of mRNA vaccination compared to the non‐immunocompromised/immunosuppressed (ISC) general population, are not well described. In a cohort of adult patients testing positive for COVID‐19 between December 10, 2020 and April 4, 2022, we compared the cumulative incidence of BTCo in a non‐ISC population to SOT recipients (overall and by organ type) using the National COVID Cohort Collaborative (N3C) including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 37 publications
2
25
1
Order By: Relevance
“…In this study, we analyzed patient-level data from a rather homogeneous cohort of OTRs, all of whom had COVID-19 in the smallest US state, during a recent time frame without significant variations in health care resources, management protocols, or circulating SARS-CoV-2 variants. Despite lower immunologic [ 12–14 ] and clinical [ 1 , 10 ] efficacy of COVID-19 vaccines among OTRs and against Omicron variants [ 20 , 21 ], we observed a strong, linear mortality and morbidity benefit with mRNA vaccination. OTRs who had received ≥3 doses had the highest survival rate and lowest rates of hospitalization and critical illness ( Table 2 , Figures 1 and 2 ).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…In this study, we analyzed patient-level data from a rather homogeneous cohort of OTRs, all of whom had COVID-19 in the smallest US state, during a recent time frame without significant variations in health care resources, management protocols, or circulating SARS-CoV-2 variants. Despite lower immunologic [ 12–14 ] and clinical [ 1 , 10 ] efficacy of COVID-19 vaccines among OTRs and against Omicron variants [ 20 , 21 ], we observed a strong, linear mortality and morbidity benefit with mRNA vaccination. OTRs who had received ≥3 doses had the highest survival rate and lowest rates of hospitalization and critical illness ( Table 2 , Figures 1 and 2 ).…”
Section: Discussionmentioning
confidence: 75%
“…The primary outcome was 90-day mortality given substantial delayed mortality among OTRs with COVID-19 [ 10 , 26 ]. Secondary outcomes were 30-day mortality, hospitalization, intensive care unit (ICU) admission, length of stay among admitted OTRs who survived at least 90 days, and peak (worst) oxygen (O 2 ) requirement on a modified ordinal scale: 0, outpatient only; 1, admitted to the hospital but without supplemental O 2 requirement; 2, low-flow O 2 requirement; 3, high-flow O 2 requirement; 4, noninvasive mechanical ventilation (BiPAP, CPAP); 5, invasive mechanical ventilation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eliminating data reporting completely during a pandemic of over 2 years duration runs counter to the SRTR mission “to provide timely and accurate information on the performance of Organ Procurement Organizations (OPOs) and transplant programs.” 3 While we agree that there were additional waves, these occurred in the setting of better understanding of non‐pharmaceutical interventions, widespread vaccination, and a therapeutic armamentarium that mitigated the associated rates of graft failure and death in our patient populations. 4 Additionally, it is unclear how we would define “significant” COVID‐19 waves in order to implement the authors' suggestion to censor data during such waves, particularly if the waves vary regionally and do not appear to have adversely impacted outcomes on a regional level. The SRC noted that, given the 2.5‐year cohorts included in the evaluations, waves have now affected all areas of the country.…”
mentioning
confidence: 99%
“…Recently, the largest breakthrough study on COVID-19 (bCOVID-19) infections in SOTR demonstrated that two doses of mRNA vaccine did not effectively mitigate the adverse effects caused by bCOVID-19 infection as in the non-immunocompromised/immunosuppressed controls, although vaccination still protected SOTR. Hence, to negate the existing naivete' in vaccine management for LT recipients, treatment, type of vaccine, patient's immune response, time, number of doses, targeted variants, and other pertinent factors should be considered [ 1 , 8 ].…”
mentioning
confidence: 99%